Digital Evidence Acquisition System on IAAS Cloud Computing Model using Live Forensic Method - Sudyana, Didik; Lizarti, Nora (Scientific Journal of Informatics, 2019)
Cloud Computing is a technological development that has been warmly discussed in recent years and has seen significant increases in usage, especially on the IAAS Cloud Computing model. The high rate of development of IAAS Cloud Computing model is in line with the high number of crimes involving IAAS Cloud Computing model on server virtualization. When a computer crime occurs and a digital forensic investigation will be carried out to uncover the case, it raises issues related to the acquisition of digital evidence. Because the acquisition model in general, it is done only to one operating system, while in virtualization there is more than one operating system, so the acquisition technique in general cannot be used because it takes only one operating system involved crime, and cannot acquire the whole data server related privacy data in other virtual operating systems. Therefore, research to make the acquisition system of server virtualization is needed. The focus in this research is to make system acquisition in server virtualization Proxmox using the live forensic method to produce a system that can acquire virtualization without disrupting the overall data server and in accordance with the principle of digital forensics. The resulting acquisition system can be a reference for investigators to investigate the IAAS Cloud Computing model on Proxmox virtualization and facilitate the investigator's work in the use of the system because the investigator simply chooses which virtual operating system to acquire, after which the system will work on its own the acquisition.